Investigating the Factors Influencing Shadow Banking in EU Member States - Petkovski, Mihail; Stojkov, Aleksandar; Kjosevski, Jordan (Eastern European economics, 2024)
This paper investigates the driving forces of shadow banking in 27 EU Member States, using annual data for 1999-2020. To account for heterogeneity, the panel is split into two sub-groups labeled "old" Europe and Eastern Europe. The estimations provide evidence that bank assets, insurance corporation assets, interest rate spreads, and regulatory quality significantly determine shadow banking growth. Financial development also has a considerable influence. The strong link between shadow banking entities and insurance corporations highlights the need to create a framework to test the interconnectedness of financial institutions at the EU level.